2005
DOI: 10.1200/jco.2005.02.4364
|View full text |Cite
|
Sign up to set email alerts
|

Phase I to II Multicenter Study of Oblimersen Sodium, a Bcl-2 Antisense Oligonucleotide, in Patients With Advanced Chronic Lymphocytic Leukemia

Abstract: Dosing with oblimersen sodium in patients with CLL is limited by development of a cytokine release syndrome that is characterized by fever, hypotension, and back pain. Oblimersen sodium has modest single-agent activity in heavily pretreated patients with advanced CLL, and further evaluation of its activity in combination with cytotoxic drugs is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(101 citation statements)
references
References 14 publications
0
98
1
1
Order By: Relevance
“…Attempts to target BCL2 in CLL cells using an antisense oligonucleotide strategy have yielded relatively modest reductions in BCL2 protein and modest clinical benefit (33). Thus, these studies have not been well suited to studying the requirement for BCL2 in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to target BCL2 in CLL cells using an antisense oligonucleotide strategy have yielded relatively modest reductions in BCL2 protein and modest clinical benefit (33). Thus, these studies have not been well suited to studying the requirement for BCL2 in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive clinical experience now exists with Genasense (G3139; Genta, Inc.), an antisense therapeutic directed against Bcl-2 ( Badros et al 2005;Marcucci et al 2005;O'Brien et al 2005;Tolcher et al 2005). Encouraging phase II trial results, including evidence of target modulation, have been reported in hormone-refractory prostate cancer and relapsed multiple myeloma (Badros et al 2005;Tolcher et al 2005).…”
Section: Targeting Apoptosis In Melanoma: Inhibiting Bcl2mentioning
confidence: 99%
“…bcl-2 antisense therapeutic strategy has proven feasible without toxicity and is already in clinical trials for B-CLL patients (O'Brien et al, 2005). Our results suggest that an approach involving also the targeting of bfl-1 deserves further testing.…”
Section: Discussionmentioning
confidence: 71%